The Concept of Leadership in Sunni and Shia Perspectives - Babgure, Hesam (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
This article aims to examine the differences and similarities in the concept of leadership from Sunni-Shia perspectives, considering both its sociological and political aspects. The research utilizes a historical research method, which involves analyzing past realities and implementing them in contemporary life. The data collection process involves gathering all relevant sources needed, focusing on scholarly literature, historical documents, and other writings related to the article. The study reveals that there are significant differences in the concept of leadership from Sunni and Shia perspectives, both theologically and sociologically. However, regarding matters of muamalah or social-political interaction, there are no differing views between Sunni and Shia perspectives